The Impact of Nomophobia on Learning Concentration and Its Management Through Guidance Counseling Services at MDTA Aek Badak - Asmaryadi; Fatma Suryani Harahap; Riski Baroroh; Fauzan Habibie Nasution; Devi Adriany; Mutiara Astari (Universitas Negeri Medan, 2025)
Current technological developments are advancing rapidly. These developments do not simply allow humans to live as usual; they have a major impact on human life. Students who do not hold or carry their cell phones feel uneasy or afraid because they do not bring their cell phones wherever they go. This term refers to nomophobia. This study uses a qualitative approach as a qualitative research design. This study will use in-depth interviews, while paying attention to data validity consisting of credibility, transferability, dependability, and confirmability. Data analysis can be carried out in various ways, ranging from data reduction, data presentation, to drawing conclusions. At MDTA Aek Badak, cell phone use has become a worrying habit. Students find it difficult to focus, become easily agitated when they do not have their cell phones, become angry when asked to stop playing, and often come to class tired because they play until late at night. Guidance and counseling are at the forefront of addressing this issue.In addressing nomophobia, guidance counselors not only provide advice but also offer emotional support to students. The guidance and counseling at MDTA Aek Badak play an important role in overcoming nomophobia by using preventive, curative, and educational approaches. Parental involvement in monitoring cell phone use at home makes it easier to change and maintain student behavior, which supports the success of guidance and counseling.